A comparison of the nutritional quality of products offered by the top packaged food and beverage companies in Canada - Laura Vergeer; Lana Vanderlee; Mavra Ahmed; Beatriz Franco-Arellano; Christine Mulligan; Kacie Dickinson; Mary R. L'Abbé (BMC, 2020)
Abstract Background Canada's food supply is abundant in less healthy products, increasing Canadians' risk of obesity and non-communicable diseases. Food companies strongly influence the food supply; however, no studies have examined differences in the healthfulness of products offered by various companies in Canada. This study aimed to compare the nutritional quality of products offered by the top packaged food and beverage companies in Canada. Methods Twenty-two top packaged food and beverage manufacturing companies were selected, representing > 50% of the Canadian market share in 2018. Nutritional information for products (n = 8277) was sourced from the University of Toronto Food Label Information Program 2017 database. Descriptive analyses examined the nutritional quality of products based on: 1) the Health Star Rating (HSR) system; 2) calories, sodium, saturated fat and total sugars per 100 g (or mL) and per reference amounts (RAs) defined by Health Canada; and 3) "high in" thresholds for sodium, saturated fat and total sugars proposed by Health Canada for pending front-of-package labelling regulations. Kruskal-Wallis tests compared HSRs of products between companies. Results Mean HSRs of companies' total product offerings ranged from 1.9 to 3.6 (out of 5.0). Differences in HSRs of products between companies were significant overall and for 19 of 22 food categories (P < 0.05), particularly for fats/oils and beverages. Calories, sodium, saturated fat and total sugars contents varied widely between companies for several food categories, and depending on whether they were examined per 100 g (or mL) or RA. Additionally, 66.4% of all products exceeded ≥1 of Health Canada's "high in" thresholds for sodium (31.7%), saturated fat (28.3%) and/or sugars (28.4%). The proportion of products offered by a company that exceeded at least one of these thresholds ranged from 38.5 to 97.5%. Conclusions The nutritional quality of products offered by leading packaged food and beverage manufacturers in Canada differs significantly overall and by food category, with many products considered less healthy according to multiple nutrient profiling methods. Variation within food categories illustrates the need and potential for companies to improve the healthfulness of their products. Identifying companies that offer less healthy products compared with others in Canada may help prompt reformulation.